Medina (Medical Instant Pashmina) Hijab for Medical Personnel - Sandrarizka Yuvike Limita; Fairuz Febrita Dinarsari; Tiga Putu Rona; Achmad Aunul Halimi (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
MEDINA (Medical Instant Pashmina) is a hijab made for medical personnel. MEDINA hijab is a hijab in instantpashmina model with a small hole near the ears but it cannot be seen from outside and the function is to makeusing stetoskop easier. The purpose of making our product is to make MEDINA as medical personnel’s hijabwhich has funct ion to easily use stethoscope and still look syar’i. It is convenient with our motto: “Beauty inSyari, Luxury in Simplicit y”. There are three stages in running this business, the first is tools and materialspreparation and also price survey, then the second is program implementation, and the third is evaluate anddetermine the next stage plans. Keywords: Hijab, Instant Pashmina, Medical Personnel